2008
DOI: 10.1016/j.juro.2008.07.067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vesicoureteral Reflux in Acute Renal Cortical Scintigraphic Lesion and Ultimate Scar Formation

Abstract: Although vesicoureteral reflux is not a prerequisite for development of acute photon defect and subsequent renal scarring, reflux itself might be an aggravating factor for acute photon defect and scar formation. There seems to be a correlation between reflux grade and frequency of acute photon defect on dimercapto-succinic acid scintigraphy but scar change occurs independently of reflux grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
4
15
1
1
Order By: Relevance
“…However, an association between urinary tract infection in children with vesicoureteral reflux and renal scarring remains unquestionable (Faust et al, 2009;Jahnukainen et al, 2005;Muinuddin et al, 2008). This was confirmed by recent studies that demonstrated an increase in the risk of renal scarring after acute pyelonephritis in patients with vesicoureteral reflux (Kanellopoulos et al, 2006;Lee et al, 2006;Polito et al, 2006;Oh et al, 2008). Studies by Svensson et al (2005) and Mohanan et al (2008) disclosed that renal scarring was detected less frequently in infants with vesicoureteral reflux and without urinary tract infection than in those with vesicoureteral reflux and urinary tract infection.…”
Section: Reflux Nephropathysupporting
confidence: 54%
See 1 more Smart Citation
“…However, an association between urinary tract infection in children with vesicoureteral reflux and renal scarring remains unquestionable (Faust et al, 2009;Jahnukainen et al, 2005;Muinuddin et al, 2008). This was confirmed by recent studies that demonstrated an increase in the risk of renal scarring after acute pyelonephritis in patients with vesicoureteral reflux (Kanellopoulos et al, 2006;Lee et al, 2006;Polito et al, 2006;Oh et al, 2008). Studies by Svensson et al (2005) and Mohanan et al (2008) disclosed that renal scarring was detected less frequently in infants with vesicoureteral reflux and without urinary tract infection than in those with vesicoureteral reflux and urinary tract infection.…”
Section: Reflux Nephropathysupporting
confidence: 54%
“…In study by Ylinen et al (2003) renal scarring was found more frequently in infants in whom vesicoureteral reflux was diagnosed after the first episode of urinary tract infection than in those in whom vesicoureteral reflux was detected antenatally. The risk of acute pyelonephritis and thus renal scarring increases along with grade of vesicoureteral reflux (Arant, 1991;Oh et al, 2008, Shaikh et al, 2010 www.intechopen.com et al, 1992). In the last years, an association between ACE gene polymorphism and development/ progression of RN was demonstrated.…”
Section: Reflux Nephropathymentioning
confidence: 99%
“…This finding strengthens the previous report that VUR is the factor associated with increased risk of scar formation from their initial insult of acute scintigraphic lesions considering other clinical factors. [17,18] Our manuscript has some limitations in the point that every child with VUR had undergone antibiotic prophylaxis which may have affected prevalence of ASL and USF in this group. In accordance with our previous report, VUR and TDT were independent risk factors for acute scintigraphic lesion and ultimate scar formation [17].…”
Section: Discussionmentioning
confidence: 97%
“…The inclusion criteria were fever (body temperature 38 C or greater), positive urine culture and pyuria. The definition of positive urine culture was either growth of microorganisms over 10 5 colonyforming units (CFU)/ml from clean-voided midstream urine or over 10 3 CFU/ml from suprapubic puncture in children with diaper voiding [18]. Any individual with a history of UTI, concurrent congenital urogenital abnormalities or uropathy other than VUR and with known prenatal hydronephrosis were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation